Damping ratio maximization in thickness direction using viscoelastic and structural materials based on constrained layer damping. Issue 3 (4th March 2022) - Inozume, Seita; Aihara, Tatsuhito
Abstract : Constrained layer damping (CLD) is a typical application known to exhibit high damping. However, the damping ratio generally attains its maximum value when the applied surface is fully covered with the damping material. In this study, a method is proposed of topology optimization in the thickness direction using viscoelastic and constrained materials based on CLD in order to obtain a higher damping ratio. A mathematical formulation is proposed of the material interpolation functions of the store elastic modulus, loss elastic modulus, Poisson's ratio and density. As a result of the optimization using a cantilever beam, the damping ratio obtained in the optimal layout is 1.44 times higher than that in conventional CLD. The higher damping in the optimal layout can be attributed to compression of the viscoelastic material by the slits, and a decrease in the flexural rigidity caused by the taper and the longitudinally extending part of the slits.